Endoscopic ischemic polypectomy for small-bowel polyps in patients with Peutz–Jeghers syndrome - Khurelbaatar, Tsevelnorov; Sakamoto, Hirotsugu; Yano, Tomonori; Sagara, Yuichi; Dashnyam, Ulzii; Shinozaki, Satoshi; Sunada, Keijiro; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy, 2020)
Background To decrease the risk of bleeding or perforation, ischemic polypectomy is performed using a detachable snare or endoclip with double-balloon endoscopy (DBE) for small-bowel polyps in patients with Peutz – Jeghers syndrome. The aim of this study was to determine the effectiveness and feasibility of ischemic polypectomy.Methods We retrospectively reviewed patients who underwent two or more sessions of ischemic polypectomy using DBE from July 2004 to August 2017.Results 67 therapeutic DBEs were performed in nine patients during the study period and 352 polyps were treated. The median observation period was 34 months (range 12 – 66). There was a declining trend over time in the median number of polyps > 15 mm treated per patient first DBE session 6, second 2, third 1.5, fourth 0.5, fifth 0.5; P = 0.11, Friedman test). No patient required laparotomy due to intussusception during the study period. One patient developed mild acute pancreatitis after the procedure.Conclusions Ischemic polypectomy was feasible for the control of small-bowel polyps in patients with Peutz – Jeghers syndrome.